Haruskah Jenjang Diploma-3 Ditingkatkan Menjadi Sarjana Terapan - Rivan Sutrisno; Mohammad Rizal Gaffar; Mamun Sutisna; Tangguh Dwi Pramono; Yayan Firmansyah (Ebiz Prima Nusa, 2022)
The Directorate General of Vocational Education, Ministry of Education and Culture, has begun to pay more attention to Vocational education. The real steps of the Directorate General of Vocational Education of the Ministry of Education and Culture can be seen from its two special programs, namely the D2 fast track program for SMK and the D-3 upgrade program to applied bachelor's degree. This study aims to provide a basis for one of the universities in Bandung to determine whether it is the right step to increase the D-3 level to become an Applied Bachelor. Quantitative Descriptive Analysis was conducted to provide a real picture of the condition of existing D-3 students. The results showed that the majority of students chose the D-3 level because they wanted to immediately graduate from college and then work. Meanwhile, students who enter the D-3 level because they are not accepted in the first choice occupy the lowest position on the D-3 level selection criteria indicator and are included in the assessment criteria. Therefore, there is still no urgency to increase the D-3 level to an Applied Bachelor degree from the perspective of higher education consumers, namely college students.